Composition-function relations of cartilaginous tissues engineered from chondrocytes and mesenchymal stem cells isolated from bone marrow and infrapatellar fat pad - KELLY, DANIEL; BUCKLEY, CONOR; VINARDELL, TATIANA (My University, 2011)
The objective of this study was to determine the functional properties of cartilaginous tissues generated by porcine MSCs isolated from different tissue sources, and to compare these properties to those derived from chondrocytes (CC). MSCs were isolated from bone marrow (BM) and infrapatellar fat pad (FP), while CC were harvested from the articular surface of the femoro-patellar joint. Culture-expanded CC and MSCs were encapsulated in agarose hydrogels and cultured in the presence of TGF-?3. Samples were analysed biomechanically, biochemically and histologically at day 0, day 21 and day 42. After 42 days in free swelling culture, mean GAG content was 1.50 % w/w in CC seeded constructs, compared to 0.95 % w/w in FP and 0.43 % w/w in BM seeded constructs. Total collagen accumulation was highest in FP constructs. DNA content increased with time for all the groups. The mechanical functionality of cartilaginous tissues engineered using CCs was superior to that generated from either source of MSCs. Differences were also observed in the spatial distribution of matrix components in tissues engineered using CC and MSCs, which appears to have a strong influence on the apparent mechanical properties of the constructs. Therefore while functional cartilaginous tissues can be engineered using MSCs isolated from different sources, the spatial composition of these tissues is unlike that generated using chondrocytes, suggesting that MSCs and chondrocytes respond differently to the regulatory factors present within developing cartilaginous constructs.
PUBLISHED
Keywords: Bioengineering; Infrapatellar fat pad; Cartilage; Mesenchymal stem cells; TGF-?3; Next Generation Medical Devices